PENGGUNAAN TEKNIK MANAJEMEN KONFLIK DALAM PEMBELAJARAN SOSIOLOGI UNTUK MEREDAM PERILAKU BERKONFLIK SISWA - Bambang Kariyawan (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
Conflicting behavior could damage the integrity of Indonesiaas a multicultural society. This conditioncan be anticipated with the social partnership process in the learning process. This study was conducted to investigate the implementation of learning with conflict management techniques and to determine whether learning with conflict management techniques can reduce conflicting behavior among students. This technique refers to the development of the theory of conflict transformation. Learning steps using this technique consists of the distribution group by using sociometry and socio-cultural background of students, conflict analysis via mass media, analysis of the impact of conflict, conflict analysis through short stories ands hort drama on social conflict themed. By using descriptive quantitative research methods, the research found that learning conflict management techniques can reduce conflicting behavior of students by engaging students to fully cooperate in performing overall steps in the conflict management techniques. The implementation of conflict management techniques can be learning alternative that can shape students behavior to be more character, by learn to appreciate the variety of differences.